Digital Service Innovation in Enhancing Customer Satisfaction: An Analysis of Service and Product Quality in the Banking Industry - Kevin Ewaldo; Prastyo, Agung; Marselinus; Aira Putri E D (Fakultas Ilmu Administrasi, 2025)
This study aims to analyze the influence of service quality and product quality on customer satisfaction through digital service innovation at BNI Agen46 Menteng Main Branch and to propose strategic recommendations for developing digital services that enhance customer satisfaction and loyalty. A quantitative approach was applied using a survey method with a five-point Likert scale questionnaire. The collected data were analyzed using multiple linear regression to examine the relationships among variables, supported by validity, reliability, and classical assumption tests to ensure the robustness of the findings. The results indicate that both service quality and product quality have a positive and significant impact on customer satisfaction. These findings highlight that improving service and product quality is crucial for strengthening customer loyalty and fostering sustainable long-term relationships. Furthermore, based on SWOT and TOWS analyses, this study proposes strategic recommendations that leverage internal strengths and external opportunities, such as optimizing brand reputation, fostering collaboration with fintech companies, and enhancing digital service features to be more responsive to customer needs.